2011
DOI: 10.1073/pnas.1016928108
|View full text |Cite|
|
Sign up to set email alerts
|

Conditional reduction of adult neurogenesis impairs bidirectional hippocampal synaptic plasticity

Abstract: Adult neurogenesis is a process by which the brain produces new neurons once development has ceased. Adult hippocampal neurogenesis has been linked to the relational processing of spatial information, a role attributed to the contribution of newborn neurons to long-term potentiation (LTP). However, whether newborn neurons also influence long-term depression (LTD), and how synaptic transmission and plasticity are affected as they incorporate their network, remain to be determined. To address these issues, we to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 28 publications
1
62
1
1
Order By: Relevance
“…These deficits were not related to a disruption of ongoing neurogenesis since at the time of killing cell proliferation was back to normal. An alteration of synaptic plasticity can be ruled out since LTP and LTD impairments are rescued completely within 4 weeks after restoring adult neurogenesis (Massa et al, 2011). The deficits that we observed were not either due to ablation of subventricular zone progenitor cells or to nonspecific effects of AraC since animals tested for a shorter delay learned the task.…”
Section: Functional Integration Of Mature Adult-born Neuronsmentioning
confidence: 70%
“…These deficits were not related to a disruption of ongoing neurogenesis since at the time of killing cell proliferation was back to normal. An alteration of synaptic plasticity can be ruled out since LTP and LTD impairments are rescued completely within 4 weeks after restoring adult neurogenesis (Massa et al, 2011). The deficits that we observed were not either due to ablation of subventricular zone progenitor cells or to nonspecific effects of AraC since animals tested for a shorter delay learned the task.…”
Section: Functional Integration Of Mature Adult-born Neuronsmentioning
confidence: 70%
“…Hence, administration of the tetracycline analog, doxycycline, increases subgranular zone apoptosis. However, neurogenesis is reduced rather than ablated in this model (Dupret et al 2008;Massa et al 2011).…”
Section: Abgcs and Pattern Separationmentioning
confidence: 71%
“…Points (1), (3), and (4) are now wellreplicated findings (Saxe et al 2007;Wang et al 2008;Garthe et al 2009;Massa et al 2011) and a study in which NR2B was genetically deleted from abGCs recently found that LTP was absent in DG field recordings (Kheirbek et al 2012a). Schmidt-Hieber et al (2004) made whole-cell recordings from young abGCs (PSA-NCAM immunoreactive) and matGCs and applied three different LTP induction protocols where u-burst afferent stimulation was paired with distinct regimes of postsynaptic depolarization (all in the presence of a GABA A antagonist).…”
Section: Afferent Synaptic Plasticitymentioning
confidence: 85%
See 1 more Smart Citation
“…These newborn neurons have biophysical characteris-tics that allow them to preferentially contribute back to synaptic plasticity, in that they have a lower threshold for the induction of LTP compared to mature neurons, due to their higher input resistance and slower membrane time constant [14,15]. Newborn neurons are also important for the induction of bidirectional hippocampal synaptic plasticity [16]. Furthermore, evidence is mounting to support the idea that adult-born neurons are integral participants in hippocampal-dependent cognitive processes, such as learning and memory formation [17][18][19], and mood regulation [20][21][22].…”
mentioning
confidence: 99%